Electrocatalysts: Recent Advances in Earth‐Abundant Heterogeneous Electrocatalysts for Photoelectrochemical Water Splitting (Small Methods 6/2017). Issue 6 (June 2017) - Hou, Yang; Zhuang, Xiaodong; Feng, Xinliang
Abstract : Recent progress regarding earth‐abundant heterogeneous electrocatalysts as substitutes for photoelectrochemical water splitting is reviewed by Xinliang Feng and co‐workers in article number1700090 . Composition/structure–activity relationships are highlighted, and perspectives on challenges and opportunities for enhancing photoelectrochemical water‐splitting performance are discussed.